Comparison of biomass and deoxynivalenol production of northern European and southern European Fusarium graminearum isolates in the infection of wheat and oat grains - Yli-Mattila Tapani; Hussien Taha; Abbas Asmaa (SPRINGER, 2022)
The 3ADON chemotype of Fusarium graminearum predominates in northern Europe, whereas the 15ADON chemotype is predominant in central and southern Europe. Therefore, it has been suggested that there are two F. graminearum populations in Europe, which may have been specialized to different host plants. The aim of the present work was to test this hypothesis by comparing southern European isolates (15ADON chemotype) from southern Russia and northern European isolates (3ADON chemotype) from Finland in the infection of grains in wheat cultivar Wellamo and oat cultivar Venla. F. graminearum biomass levels were measured by TaqMan (2018) and SYBR Green (2019) qPCR, while DON levels were measured by chromatographic methods. Most of the qPCR and DON results are supporting the hypothesis that in F. graminearum the 15ADON isolates from southern Russia are more specialized to wheat than the 3ADON isolates from Finland. In oat, there were not as clear differences between the 15ADON and 3ADON isolates, but in 2018 higher F. graminearum DNA levels and in 2019 higher DON and F. graminearum DNA levels were found in oat samples inoculated with 3ADON isolates. Our results are in line with literature according to which F. graminearum DNA and DON levels are also highest in oat in northern Europe, while in southern Europe they are highest in wheat and maize.